Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Jerry Probst, December 17, 1988 - Probst, Jerryet al (1988)
Iowa Christmas bird counts of species found in Sioux City contributed by Jerry Probst, December 17, 1988. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1988-1989. Epson - sheet feed